STRATEGI PEDAGANG KAKI LIMA DALAM MENINGKATKAN PENJUALAN UNTUK KESEJAHTERAAN KELUARGA ( STUDI KASUS PEDAGANG KAKI LIMA DI JALNA LALU MESIR KELUARAHAN BABAKAN ) - Laras Widia Astuti; Rosita, Rosita; Sahar, Sahar (Nusantara Hasana Journal, 2025)
This research is entitled "START VENDORS' STRATEGIES IN INCREASING SALES FOR FAMILY WELFARE (CASE STUDY OF STREET VENDORS ON THE STREETS OF EGYPT, BABAKAN VILLAGE)" The problem raised in this research is what strategies are used by street vendors in increasing income for family welfare on the streets Lalu Egypt, Babakan Village, what obstacles do street vendors face on Jalan Lalu Egypt, Babakan Village and how do they deal with the obstacles they face and here the researcher wants to know the strategies used by street vendors in increasing sales for family welfare on Jalan Lalu Egypt, Babakan Village and want to know the obstacles and how to deal with the obstacles faced by street vendors using a descriptive approach. The data collection method used was the results of interviews, documentation. Based on the research results, it can be concluded that the strategy used by street vendors on the streets of Egypt in Babakan sub-district is to carry out promotions through social media, maintain product quality, and choose strategic locations and the obstacles faced by street vendors are business location and weather factors and to overcome obstacles, namely by providing the best service to buyers.